Perfil dos pacientes com leucemia linfocítica aguda e linfoma não-Hodgkin em um hospital público pediátrico do Ceará - Sousa, Socorro Maria Pedro de (2007)
The Acute Lymphocytic Leukemia (ALL) and the Non-Hodgkin Lymphoma (NHL) are among the most frequent types of cancer in children. The prevention and control of the cancer must be prioritized, in view of its high prevalence and increasing relevance as cause of death in many countries, beyond the great sum of consumed financial resources. The Brazilian northeast is poor in epidemiological studies about cancer in the children. The objective of this paper was to set the profile of the patients with LLA and LNH admitted in the Hospital Infantil Albert Sabin between 2001 and 2005. Observational descriptive and retrospective study. 325 medical registers (254 cases of LLA and 71 of LNH) of patients among 0 and 18 years and 11 months had been revised. The data had been inserted in data bases of the programs SPSS 14.0, Epi 3.3.2 Info and Microsoft Excel 2007. A Z-score cut-off point of <-2 SD was used to classify the malnutrition. The Fisher’s Exact Test, Qui-square, Student (t), Mann-Whitney, Shapiro-Wilk, Levene, Log-rank, Cox regression and Kaplan Meier Survival Probability Estimates were used in the statistical analyses. The level of significance was p<0,05. The population of this study was predominantly male (63.4%), 02 to 06 years age-group (49.8%), non-white (62.5%), from the capital and metropolitan region (56.9%) and with prognostic of high risk (59.1%). 38.3% died. The main clinical manifestations had been fever, anaemia, loss of weight and fatigue in the LLA cases; and fever, anaemia, palpable tumor mass and abdominal pain in the LNH cases. The mean duration time of the complaints was 3.9 months. Children with 0 to 1 and 13 to 18 years had presented worse prognosis. The color of the skin, the prognosis, the treatment protocol and the initial clinical manifestations (fever, fatigue and vomit) had shown significant association in relation to the deaths. The therapeutical protocols more used were adapted of the LLA 93 and LNH 95. 31% of the patients in use of LLA 93 and 49.2% in use of LNH 95 died. The largest percent of deaths were in the group of high risk (56.94%) and in the induction phase (36.11%) of protocol LLA 93. Between the patients of low risk, 39.28% died during the maintenance phase and 17.85% after the end of the protocol. 48.78% of the patients of high risk died during the induction phase. Among the 25 cases that used protocol LNH 95 and died, 4% corresponded to lymphoma of high risk deriving of the cells T and 96% of the cells B. 53.31% (n=15) of the patients with lymphoma of the cells B and intermediate risk to fallen died during the Cycle A of the treatment. Nine patients presented high risk for fallen and 33.34% died in the cytoreduction phase. The malnutrition indices to the LLA patients were of 8.3%, 6.0% and 5.6% and to LNH were 12.3%, 14.1% and 15.9% in relation the weight/height, weight/age and height/age, respectively. Patients with LLA had presented larger deficit in the index weight/height, indicative of a process of acute malnutrition. Larger deficit in the height/age index between the patients with LNH indicates a process of chronic malnutrition. The results about the frequency of these disease, age-group and gender were equivalents to those encountered in the majority of studies. The initial prognosis and the therapeutical protocol indicate an influence on the outcome of the treatment. Other studies are necessary to evaluate the influence of the chemotherapy, color of the skin, nutritional status and other factors on the survival time of the patient with cancer. The professionals of health and the laypeople need to know better and to be intent to the initial clinical manifestations of the neoplasm disease in order to facilitate the precocious diagnosis.